Interpersonal Communication Between Parents and Children Regarding Kafa'ah Standards in the Selection of a Life Partner - Dony Rano Virdaus; Lukman Hakim; Irnawati Apriliya; Sofia Nadiva (Bahasa Indonesia, 2025)
This study aims to describe patterns of interpersonal communication between parents and their daughters when defining kafa’ah standards for prospective spouses within pesantren environments. This focus emerged from a research gap in previous studies, which emphasised the normative dimension of kafa’ah rather than the communicative dynamics within santri families. A qualitative approach was adopted, involving field research and the collection of primary data through in-depth interviews and observations with four families of female students (santri) from Darussalam Islamic Boarding School in Kediri. Secondary data were obtained from relevant books, journals and other documented sources. Both types of data were analysed using in-depth analytical techniques, revealing that open and persuasive communication is the dominant pattern through which parents and children negotiate and align their views on kafa’ah standards. Mutual understanding is further reinforced through two-way interactions grounded in pesantren moral values and shared spiritual experiences. These findings contribute to the discourse on interpersonal communication in pesantren settings by demonstrating that religiosity functions as both a value system and a communicative framework that mediates family decision-making processes.